(untitled) (Global Journal of Management and Business Research, 2020)
Global businesses and economic activities have gone digital and nations are shifting rapidly, fast adjusting all legal and regulatory frameworks to keep pace with realities. This is as true for the corporate bodies doing business in Nigeria as it is for audit-related issues. Consequently, the Companies and Allied Matter Act (CAMA) was revised to provide a more robust framework for restructuring identified legal, regulatory, and observed administrative bottlenecks. On this basis, this study examined revised Nigerian Company Law 2020, matter arising from audit issues. In carrying out this objective, exploratory research approach was adopted, as write-ups, journals, periodicals, and material related to this study were reviewed.